Sero-prevalence and determinants of Hepatitis B among a cohort of HIV-infected women of reproductive age in Nigeria. - Olusegun Adewale Adeyemi; Ijeoma Uchenna Itanyi; Chamberline Ekene Ozigbu; Nicole Stadnick; Kiyomi Tsuyuki; Olanrewaju Olayiwola; Amaka Grace Ogidi; Chuka Eze; Gregory Alan Aarons; Chima Ariel Onoka; Echezona Edozie Ezeanolue (PLoS ONE, 2020)
Introduction Sub-Saharan Africa houses over two-thirds of the 37 million people living with human immunodeficiency virus (HIV) globally and of this, 5-20% are co-infected with Hepatitis B virus (HBV). This is double jeopardy, especially for women of reproductive age in these settings, who can transmit both viruses vertically as well as horizontally to their children. The objectives of this study were to investigate the prevalence and determinants of HBV among women of reproductive age living with HIV. Methods This was a cross-sectional study of HIV-infected women of reproductive age in Benue State, Nigeria. Participants were eligible for the study if they were HIV-infected women (ages 18-45 years) receiving care from any of the selected study sites. A global rapid hepatitis B surface antigen (HBsAg) antibody test strip was used to test for HBsAg in plasma. A pretested questionnaire was used to collect data on sociodemographic, clinical and lifestyle characteristics of participants. We estimated prevalence of HBV infection and used multivariable logistic regression to determine factors associated with the infection at a significance level of <0.05. Results A total of 6577 women were screened for HBsAg. The prevalence of HBV was 10.3% (95% CI: 9.5-10.9%). Age, parity and male partner's HIV status were found to be associated with having HBV infection. Compared to women older than 40 years, the odds of HBV infection increased significantly with increasing age until age 35 years and decreased significantly with increasing parity (versus no parity). Women with HIV-infected partners and those without a partner had higher odds of HBV infection compared to women with HIV-negative partners. Conclusion HBV is hyperendemic among HIV-infected women of reproductive age in North Central Nigeria. Specific programs targeting HBV testing, vaccination and treatment of all women of reproductive age need to be developed in this resource-limited, high-need setting.